Government Subsidies and Patent Race Strategies: A BI-Objective Portfolio Optimization Model for Communication Technology Innovation - Ji Wang; Chunming Xu (Decision Making: Applications in Management and Engineering, 2025)
This study examines the strategic challenges encountered by communication enterprises engaged in government-subsidised patent competitions, where the effective distribution of R&D resources is essential to offset competitive disadvantages. To address this issue, a bi-objective portfolio optimisation model is proposed, aiming to maximise net returns while simultaneously reducing semi-absolute deviation risk, with consideration of substitution costs and policy-driven subsidies. Using MATLAB-based numerical simulations, the analysis demonstrates that firms with weaker competitive positions can improve their performance in patent races by reallocating investments across significant technological areas in line with their varying levels of risk tolerance. The findings further suggest that when firms possess greater autonomy in decision-making, concentrating resources in core self-interest technologies enhances their chances of achieving success in patent races. Overall, the research contributes theoretical and practical perspectives on R&D portfolio management within policy-supported incentive frameworks.